Genome biology of the darkedged splitfin, Girardinichthys multiradiatus, and the evolution of sex chromosomes and placentation - Du, Kang; Pippel, Martin; Kneitz, Susanne; Feron, Romain; da Cruz, Irene; Winkler, Sylke; Wilde, Brigitta; Avila Luna, Edgar G.; Myers, Gene; Guiguen, Yann; Macias Garcia, Constantino; Schartl, Manfred (Genome Research, 2022)
Viviparity evolved independently about 150 times in vertebrates and more than 20 times in fish. Several lineages added to the protection of the embryo inside the body of the mother, the provisioning of nutrients, and physiological exchange. This often led to the evolution of a placenta. Among fish, one of the most complex systems serving the function of the placenta is the embryonal trophotaenia/ovarian luminal epithelium of the goodeid fishes. For a better understanding of this feature and others of this group of fishes, high-quality genomic resources are essential. We have sequenced the genome of the darkedged splitfin, Girardinichthys multiradiatus. The assembly is chromosome level and includes the X and Y Chromosomes. A large male-specific region on the Y was identified covering 80% of Chromosome 20, allowing some first inferences on the recent origin and a candidate male sex determining gene. Genome-wide transcriptomics uncovered sex-specific differences in brain gene expression with an enrichment for neurosteroidogenesis and testis genes in males. The expression signatures of the splitfin embryonal and maternal placenta showed overlap with homologous tissues including human placenta, the ovarian follicle epithelium of matrotrophic poeciliid fish species and the brood pouch epithelium of the seahorse. Our comparative analyses on the evolution of embryonal and maternal placenta indicate that the evolutionary novelty of maternal provisioning development repeatedly made use of genes that already had the same function in other tissues. In this way, preexisting modules are assembled and repurposed to provide the molecular changes for this novel trait.
10.1101/gr.275826.121